Calculations and Evaluations of the n+48Ti Reaction Below 200 MeV. (4th March 2021) - Su, Xinwu; Xu, Yongli; Han, Yinlu
Abstract: The medium-mass structural material titanium has been extensively applied in the nuclear reactor systems of fission or fusion, and related data are also urgently needed. In the present work, all reaction cross sections, angular distributions, energy spectra, and double-differential cross sections are consistently calculated and analyzed for the n+ 48 Ti reaction below 200 MeV. The theoretical calculations are compared with the experimental data, together with the evaluated results in the ENDF/B-VIII.0, JENDL-4.0, and JEFF-3.3 libraries. In general, these results provide a satisfactory description of the corresponding experimental data.